Ovartaci the signature of madness - Hansen, Brian Benjamin (Aarhus University Press, 2022)
Hospitalized following a mental health crisis in 1929, Louis Marcussen (1894-1985) begins a spectacular journey. He starts to produce paintings, papier mâché dolls, magical smoking devices, and mechanical objects; he starts to decorate and paint almost everything around him. He fills his room at the psychiatric institution with artworks, notably featuring tall and eloquent female figures, and he seems to invest himself deeply in his work and visions. He dissolves into a swirl of male, female, animal and divine identities. He discards the name "Louis" and takes the name "Ovartaci". The Signature of Madness' is the first international monograph on Ovartaci, and it is the first research-based book on the artist. Richly illustrated, the book reveals the world of Ovartaci. It investigates the madness of Louis and the invention of Ovartaci. It puts Louis turning into Ovartaci on the psychoanalytical couch to listen to what haunts him, as well as to describe, analyze and theorize the way in which Louis reconfigures as Ovartaci and comes to inhabit life anew. Ovartaci is increasingly recognized as one of the most enthralling Danish artists of the 20th century. At the 2022 Venice Biennale, the art of Ovartaci is part of the main exhibition and displayed in the Central Pavilion
Keywords: Ovartaci -- 1894-1985; Papiermaché; Malerei